EFFECT OF THE NUMBER OF COMMISSIONERS AND PROPORTION OF INDEPENDENT COMMISSIONERS ON PUBLIC COMPANY PERFORMANCE - Ida Masriani; Rahmat Setiawan; Wisnu Wibowo (STIE PGRI Dewantara Jombang, 2022)
This study examines whether the size of the board of commissioners and the proportion of independent commissioners affect the company's financial performance. This study uses a quantitative method with econometric calculations. Data were obtained from 236 companies listed on the Indonesia Stock Exchange in 2015-2019. The data were analyzed using panel data regression using three variables: the dependent variable ( dependent ), the independent variable ( independent ), and moderating variable. This research uses MRA ( Moderated Regression Analysis ) analysis technique which will be processed using STATA. This study proves that the size of the board of commissioners and the proportion of independent commissioners positively affect the company's financial performance. The test also involves a moderating variable in the form of government ownership. It results that the government ownership variable has no significant effect on the relationship between commissioners and financial performance. The findings of this study contribute as recommendations to stakeholders involved in the management of the company, especially public companies